2002
DOI: 10.1128/mcb.22.8.2472-2486.2002
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Endotoxin Sensitivity in Fps/Fes-Null Mice with Minimal Defects in Hematopoietic Homeostasis

Abstract: The fps/fes proto-oncogene encodes a cytoplasmic protein tyrosine kinase implicated in growth factor and cytokine receptor signaling and thought to be essential for the survival and terminal differentiation of myeloid progenitors. Fps/Fes-null mice were healthy and fertile, displayed slightly reduced numbers of bone marrow myeloid progenitors and circulating mature myeloid cells, and were more sensitive to lipopolysaccharide (LPS). These phenotypes were rescued using a fps/fes transgene. This confirmed that Fp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
76
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(83 citation statements)
references
References 96 publications
6
76
1
Order By: Relevance
“…Fes Ϫ/Ϫ macrophages exhibited defects in cell adhesion and GM-CSF signaling, pointing to incomplete maturation of their myeloid compartment. However, targeting of the Fes locus using a different strategy did not reveal alterations in the macrophage or granulocyte populations (43). This low penetrance of the Fes Ϫ/Ϫ phenotype may be a result of functional redundancy.…”
Section: Discussionmentioning
confidence: 92%
“…Fes Ϫ/Ϫ macrophages exhibited defects in cell adhesion and GM-CSF signaling, pointing to incomplete maturation of their myeloid compartment. However, targeting of the Fes locus using a different strategy did not reveal alterations in the macrophage or granulocyte populations (43). This low penetrance of the Fes Ϫ/Ϫ phenotype may be a result of functional redundancy.…”
Section: Discussionmentioning
confidence: 92%
“…Generation and genotyping of in-bred SVJ/129-CD1 hybrid lines harboring targeted null ( fps À/À ), targeted catalytically inactive ( fps KR/KR ), or transgenic ( fps Tg ) fps alleles in a targeted fps-null genetic background ( fps À/À fps Tg ) have been reported previously (6)(7)(8). Generation of in-bred transgenic mice with mouse mammary tumor virus-long terminal repeat-directed, mammary epithelial-specific expression of polyoma virus middle T antigen (PyVmT) has also been described (9).…”
Section: Methodsmentioning
confidence: 99%
“…Other possible c-Fes interactions are summarized in literature (Ferrari et al, 1995;Smithgall et al, 1998;Greer, 2002). Gene targeting experiments in mice have demonstrated that myelopoiesis is not substantially affected by the lack of c-Fes activity or c-Fes (Hackenmiller et al, 2000;Zirngibl et al, 2002). On the other hand, the Hackenmiller group has recently shown, in a further work, that truncation of c-Fes via gene targeting results in embryonic lethality and hyperproliferation of hematopoietic cells (Hackenmiller and Simon, 2002).…”
Section: Introductionmentioning
confidence: 99%